The Use of Swear Words Among Class Students (A Case Study in English Literature Study Program of Batch 2020) - Farihan, Fachrul Al; Djauhari, Otong Setiawan; Saehu, Andang (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2024)
This study aims to identify the factors that lead students to use swearwords and to find out how students feel when they do so. The research was conducted on B-class students of the English Literature study program at UIN Sunan Gunung Djati Bandung during the 2020 academic year. This research employed a qualitative research method with a case study design, describing the data narratively. Six respondents were interviewed using ten items to identify the factors and feelings associated with the use of swearwords. The study found that the use of swearwords is dominantly triggered by negative emotions like anger and discomfort, which are worsened by entertainment media and surrounding culture. Surprisingly, two participants discovered that their game teammates strongly supported using swearwords. Further, people's reactions and moods after swearing vary from harmony to silence, depending on the situation at hand. These findings emphasize the long-term impact of swearing on social perceptions and interpersonal relationships, highlighting a comprehensive approach to understanding and managing sensitive communication behaviors.